DC vacuum breakdown in an external magnetic field - Lebedynskyi, S.; Karpenko, O.; Kholodov, R.; Baturin, V.; Profatilova, Ia; Shipman, N.; Wuensch, W. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2018)
The subject of the present theoretical and experimental investigations is the effect of the external magnetic field induction on dark current and a possibility of breakdown. The generalization of the Fowler–Nordheim equation makes it possible to take into account the influence of a magnetic field parallel to the cathode surface on the field emission current. The reduction in the breakdown voltage due to the increment in electron-impact ionization was theoretical predicted. Experimentally shown that the presence of a magnetic field about a tenth as a large as the cutoff magnetic field (Hull, 1921) reduces the breakdown voltage by 10% to 20% for practically all cathodes no matter what their surface treatment.